Analisis Komparatif Metode Pembuatan Cahaya Matahari Untuk Modul Fotovoltaik Berdasarkan Studi Literatur - Athallah, Muhammad Rafi; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2026)
The testing and evaluation of the performance of photovoltaic (PV) modules of different brands and types are imperative for acquiring the higher efficiency of solar energy conversion under different conditions. [Other Content]Read: BCI survey about Artificial Intelligence may have impacted those data+Sing up to be the first to know Eclipse+ Live 1For related articles:Artificial Sunlight [BCI]Artificial Sunlight For Artificial IntelligenceArtificial Sunlight: Reconstructing Data from Sunlight Simulation [Sci Graph]Artificial Sunlight: Ways to Understand Your Computer[How]At the same time, natural sunlight can be an obstacle to getting accurate, consistent data under similar environmental conditions so sundlight simulators are used to replicate controlled lighting conditions. So far, different types of solar light simulators have been developed, including halogen, xenon and LED lamps, each possessing advantages and disadvantages in terms of light spectrum, intensity, stability, and energy efficiency. However, there is no systematic comparative assessment of how each method simulates the photon spectrum of sunlight and its stability, and this has made it challenging for the scientific community to select the most suitable method. This study introduces a research deficit by directly comparing the spectrum accuracy, intensity stability, and sensitivity to environmental factors for each type of sunlight simulator. To overcome this gap, the objective in this study is to analyze and compare the performance of halogen, xenon, and LED simulators for identifying the most effective method for testing the electrical characteristics of PV modules inside the laboratory.